Cholesterol efflux capacity is associated with lipoprotein size and vascular health in mild to moderate psoriasis - Berg, Alexander R.; Petrole, Rylee F.; Li, Haiou; Sorokin, Alexander V.; Gonzalez-Cantero, Alvaro; Playford, Martin P.; Mehta, Nehal N.; Teague, Heather L. (Frontiers in Cardiovascular Medicine, 2023)
Background and Objective: Psoriasis is a systemic inflammatory condition with poor cholesterol transport measured by cholesterol efflux capacity (CEC) that is associated with a heightened risk of cardiovascular disease (CVD). In psoriasis patients, we sought to characterize the lipoprotein profile by size using a novel nuclear magnetic resonance algorithm in patients with low CEC compared to normal CEC. Methods: Lipoprotein profile was assessed using the novel nuclear magnetic resonance LipoProfile-4 deconvolution algorithm. Aortic vascular inflammation (VI) and non-calcified burden (NCB) was characterized via positron emission tomography-computed tomography and coronary computed tomography angiography. To understand the relationship between lipoprotein size and markers of subclinical atherosclerosis, linear regression models controlling for confounders were constructed. Results: Psoriasis patients with low CEC had higher more severe psoriasis (p=0.04), VI (p=0.04) and NCB (p=0.001) concomitant with smaller high-density lipoprotein (HDL) (p=<0.001) and low-density lipoprotein (LDL) particles (p=<0.001). In adjusted models HDL size (β=-0.19; p=0.02) and LDL size (β=-0.31; p=<0.001) associated with VI and NCB. Lastly, HDL size strongly associated with LDL size in fully adjusted models (β=-0.27; p=<0.001). Conclusion: These findings demonstrate that in psoriasis, low CEC associates with a lipoprotein profile comprised of smaller HDL and LDL particles which correlates with vascular health and may be driving early onset atherogenesis. Further, these results demonstrate a relationship between HDL and LDL size and provide novel insights into the complexities of HDL and LDL as biomarkers of vascular health.